2004
DOI: 10.1074/jbc.m404328200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of TRAF6 with MAST205 Regulates NF-κB Activation and MAST205 Stability

Abstract: The binding of immune complexes to macrophage Fc␥ receptor results in a subsequent inhibition of lipopolysaccharide-stimulated interleukin-12 synthesis without affecting the induction of tumor necrosis factor-␣. RNA interference targeting MAST205, a 205-kDa serine/ threonine kinase, and transfection of dominant negative MAST205 mutants also mimic this type II macrophage phenotype. Our previous epistasis experiments suggested that the position of MAST205 in the TLR4 signal pathway was proximal to the I B kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 47 publications
(40 reference statements)
1
26
0
Order By: Relevance
“…Most members of the MAST family are ubiquitously expressed but their expression is highest in the brain (5). MAST2, the most studied member of this family, is involved in immune reactions, more specifically in the regulation of NF-κB (6). Based on this knowledge, we performed a knockdown of MAST3 in HEK293 cells and tested transcription factor NF-κB activity through reporter assays.…”
Section: Introductionmentioning
confidence: 99%
“…Most members of the MAST family are ubiquitously expressed but their expression is highest in the brain (5). MAST2, the most studied member of this family, is involved in immune reactions, more specifically in the regulation of NF-κB (6). Based on this knowledge, we performed a knockdown of MAST3 in HEK293 cells and tested transcription factor NF-κB activity through reporter assays.…”
Section: Introductionmentioning
confidence: 99%
“…The type IIa Na-dependent phosphate transporter in the renal proximal tubule is shown to interact with MAST205 (10). Recent studies suggested a role of MAST205 in interleukin-12 synthesis and NF-B activation via interaction with TRAF6 (32,38). MAST205 also interacts with protocadherin LKC, which induces contact inhibition of cell proliferation (23).…”
Section: Discussionmentioning
confidence: 99%
“…Such a complex can also be a target for therapeutic interventions in diarrheal diseases because down-regulation of MAST205 activates NHE3 and inhibits CFTR channel function. Xiong et al (24) identified a peptide from the N terminus of MAST205 that inhibits the lipopolysaccharide-stimulated activation of NF-B. It is reasonable to speculate that MAST205 peptides or small molecules that inhibit the binding of MAST205 to CFTR have the potential to combat diarrheal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…MAST205 has a serine/threonine protein kinase domain and a PDZ domain. MAST205 has been shown to interact with several proteins, including ␤2-syntrophin, protocadherin LKC, and the Na ϩ /H ϩ exchanger NHE3 (21)(22)(23)(24)(25). It has been reported that MAST205 forms a complex with TNF receptor-associated factor 6, an E3 ubiquitin ligase, resulting in the inhibition of TNF receptor-associated factor 6 activation.…”
mentioning
confidence: 99%